2019
DOI: 10.1002/aoc.5333
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of common cocatalysts in Ziegler–Natta‐catalyzed olefin polymerization

Abstract: In this study, density functional theory (DFT) molecular modeling studies were performed to explore mechanisms underlying the interactions of cocatalysts in Ziegler–Natta olefin polymerization using a range of commercially available cocatalysts, namely, trimethylaluminum (in monomeric and dimeric form, Al2Me6), dimethylaluminum chloride (in monomeric and dimeric form, Al2Me4Cl2), and triisobutylaluminum. In this regard, after exploring structural and electronic features of cocatalysts, by steric maps and conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…The residual Ti amount decreased progressively with increasing temperature, from ≈70% at 40 °C to ≈35% at 100 °C (Figure a and Table S1 (Supporting Information)); this observation is consistent with the DFT-D conclusion that TiCl 4 adsorption on MgCl 2 is weak . One can speculate that the (more) strongly bound Ti fraction features, at least in part, species in lower oxidation states (mainly Ti­(III) , ) resulting from the alkylation/reduction of TiCl 4 by AlEt 3 , which is also known to be fast. ,,,,, It may be worthy to recall that previous experimental studies demonstrated that the fraction of TiCl 4 lost to the liquid phase is practically inactive in propene polymerization …”
Section: Resultssupporting
confidence: 82%
“…The residual Ti amount decreased progressively with increasing temperature, from ≈70% at 40 °C to ≈35% at 100 °C (Figure a and Table S1 (Supporting Information)); this observation is consistent with the DFT-D conclusion that TiCl 4 adsorption on MgCl 2 is weak . One can speculate that the (more) strongly bound Ti fraction features, at least in part, species in lower oxidation states (mainly Ti­(III) , ) resulting from the alkylation/reduction of TiCl 4 by AlEt 3 , which is also known to be fast. ,,,,, It may be worthy to recall that previous experimental studies demonstrated that the fraction of TiCl 4 lost to the liquid phase is practically inactive in propene polymerization …”
Section: Resultssupporting
confidence: 82%
“…45 The same results were obtained by Fallah et al, when the AlMe 3 and AlMe 2 Cl species coordinated near the Ti active site on the (110) surface. 46 Since the external donor alkoxysilane is always used in combination with the cocatalyst AlR 3 during the polymerization, it is obvious that the AlR 2 Cl species can affect olefin insertion in the presence of the external donors.…”
Section: Introductionmentioning
confidence: 99%
“…[40,41] These bonds make PAO susceptible to cleavage at high temperature of application, which deteriorates PAOs unique characteristics and decreases its shelf life. [42,43] To overcome this drawback, PAO hydrofinishing, as an essential stage in its production, is usually accomplished. This stage needs harsh environment with high temperature and H 2 pressure (nearly above 200 C and 25 bar), which increases the risk and cost of PAO production.…”
Section: Introductionmentioning
confidence: 99%